Synergistic effect of UV light and sanitizers on the survival of Listeria monocytongenesi biofilms - Jones, Jennifer; Mendez, E.; Trinetta, Valentina; Jones, Cassandra K. (My University, 2019)
INTRODUCTION: The use of hurdle technology represents a promising method to control biofilm growth and prevent contamination within food processing plants. Listeria monocytogenes is a psychrotrophic foodborne pathogen known in the food industry for its ability to form biofilms. PURPOSE: The objective of this research was to evaluate the effect of UV light alone or in combination with different sanitizers: peracid acid (PA), quaternary ammonium (QA) and lactic acid (LAC) on the survival of L. monocytogenes biofilms on stainless steel (SS) surfaces. METHODS: A Center for Disease Control (CDC) biofilm reactor was used to grow three-day-old multi-strains L. monocytogenes biofilms on SS coupons. Treatments were applied individually (UV light or sanitizer) and in combination. SS coupons were exposed to UV light (254nm) for 15 or 30 min and to PA (190ppm), QA (389ppm) and LAC (4%) for 10 minutes. A control treatment was also evaluated. Experiments were conducted in triplicates and significant differences (P<0.05) were assessed. RESULTS: There was no difference between 15- and 30-minutes exposure to UV light (P>0.05) and a reduction of 2.0 and 1.8 log CFU/cm2 was observed as compared to the control, respectively. LAC and QA combined with 30- minutes UV light presented 1 log CFU/cm2 greater reduction than sanitizers alone (P<0.05), hence suggesting a synergistic effect. PA alone or in combination did not present a synergistic effect (P>0.05). CONCLUSION: This study shows a possible synergistic effect between LAC or QA with UV light. LAC and PA alone or in combination with UV were the most effective in reducing L. monocytogenes biofilms on (SS) surfaces.
Keywords: Spring 2019